IN-OVULE EMBRYO CULTURE OF Thermopsis turcica - D. Tekdal; S. Cetiner (Journal of Animal and Plant Sciences, 2014)
The possibility of micropropagation for the endangered Thermopsis turcica wasinvestigated through an fruit ovule-embryo culture. This technique prevents embryo degradation at the early development stage, shortens breeding time, and enables efficient propagation of many plants from a single embryo, thus avoiding for breaking seed dormancy. Although a number of efficient propagation protocols of T. turcica has been reported for multiple shoot induction and plantlet regeneration from the seeds of T. turcica, to date no publication exists on any protocol on embryo culture of T. turcica. This paper reports on the optimisation of protocols for culturing of T. turcica fruit embryos. The protocol for embryo culture used in this research consisted of cracking the fruit, pitting it to remove the seed, excising the ovule-embryo from the seed, placing it on the medium modified from established Fabaceae embryo tissue culture media, extracting embryos from ovular integuments, and culturing. In the present study, extracted ovule-embryos were cultured on a Murashige and Skoog’s medium supplemented with Zeatin (0.5 mg L-1), Giberellic acid  (0.5 mg L-1), and Indole-3-acetic acid (0.2 mg L-1). Excised embryos from the ovular integuments were maintained on Giberellic acid-free MS medium. During culturing, cotyledons began to arise and grow plantlets. Regenerated plantles were rooted on a MS medium with Indole-3-butyric acid (2.0 mg L-1). These results show that embryo culture technique can be an alternative ex-situ conservation technique for in vitro propagation of the threatened rare plant species T. turcica.
Keywords: Micropropagation; fabaceae; seed; rare plant species; tissue culture media